kırk yaş üstü akut apandisitlerde kolon motilitesindeki yavaşlama bir neden olabilir mi? - PİRALİYEV, Elnur (Bezmialem Vakıf University, 2019)
Introduction: The incidence of acute apandicitis (AA) increases in elderly people and the etiology is unknown. In this study, colonic transit time measurement with colonoscopy was performed in patients who underwent appendectomy for AA.

{{abstract}}
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of General Surgery, Istanbul, 2020
Keywords: Genel Cerrahi = General Surgery; Department of General Surgery; Genel Cerrahi Anabilim Dalı